Edge chipping resistance of veneering composite resins. (April 2021) - Zadeh, Parissa Nassary; Stawarczyk, Bogna; Hampe, Rüdiger; Liebermann, Anja; Mayinger, Felicitas
Abstract: Objectives: To investigate the edge chipping resistance (ECR) of six veneering composite resins after different treatment protocols. Materials and methods: Rectangular bar specimens were manufactured from Ceramage Incisal (CER; Shofu), dialog Vario Occlusal (DIA; Schütz Dental), Gradia Plus Heavy Body Enamel (GRA; GC Europe), in:joy incisal (INJ; Dentsply Sirona Deutschland), SR Nexco Paste Incisal (SRN; Ivoclar Vivadent), and Signum composite enamel (SIG; Kulzer). ECR was determined after five treatment protocols: (1) no treatment, (2) after storage in distilled water at 37 °C for 7 days, (3) storage in distilled water with an additional 10 000 thermal cycles (5 °C/55 °C), and hydrothermal treatment at 134 °C at a water vapor pressure of 0.2 MPa for a duration of (4) 3.5 min or (5) 23.5 min. Force was applied with the universal testing machine ZHU 0.2 (Zwick Roell) mounted with a Vickers diamond indenter until the chip fractured off the specimen and ECR values were computed by dividing the applied maximum force by the distance to the center of the applied force. Fracture analysis was performed employing light microscope imaging. Univariate and one-way ANOVA, Scheffé and Tukey-B post hoc, and partial eta squared (ƞp 2 ) were computed (p < 0.05). Results: DIA presented consistently high ECR values, while CER showed low results. For some groups, seven days' storage in water and hydrothermal treatment for 3.5 min led to higher ECR results than observed in the initial state, while an additional 10 000 thermal cycles and hydrothermal treatment for 23.5 min resulted in lower ECR values. Conclusions: The examined veneering composite resins differed in regard to their mechanical properties, with DIA possessing the highest resistance to chipping. While post-processing can initially increase a material's edge chipping resistance, intensified treatment protocols reduced the mechanical properties of veneering composite resins.